The Analysis of Strain Distribution on Corrected Varus Knee under Walking Load Condition - Yanin Ruangrittisak (2020)
© Published under licence by IOP Publishing Ltd. The knee is one of the important joint of human body to carry the body load. The deformities of knee joint affect the human activities. To treat the deformity knee, close-wedge High Tibial Osteotomy (HTO) was one of the popular techniques to adjust the strain distribution on the deformity knee close to the normal by shifting the mechanical axis toward the lateral side. This research aims to evaluate the strain distribution on the varus knee corrected by zero degree, three degrees valgus and three degreesvarus close-wedge HTO under walking load. The result was shown the lowest strain distribution occur on the three degreesvarus model following by zero degree and three degree valgus model respectively. The surgeon should be correct the varus knee by three degreesvarus close-wedge HTO to get the strain distribution on the bone closet to the normal knee.